DEVELOPING LOCAL LEADERSHIP SKILLS THROUGH COUNSELING FOR EFFECTIVE IMPLEMENTATION OF COMMUNITY DEVELOPMENT PROJECT IN NIGERIA - Saidu, Gali (Sokoto Educational Review, 2011)
Challenges associated with local communities in Nigeria have created a need for a strong and sound local leader. However, despite growing support for the development of communities of the local level, little is known about the counselling impact in the development of local leaders for effective implementation of community development projects (CDP). Consequently, the need for developing local leadership skills through counselling can serve as an attempt to make a scratch on the counselling impact towards the implementation of CDP especially due to the perceived challenges associated with developing local leadership skills that manage CDP. It is against this backdrop the paper set to address local leadership roles, identification of local leadership in CDP, counselling strategy for developing local leadership for implementation of CDP, and developing local leadership skills through counselling for implementation of CDP.